Diplomacy in reporting: the Sulu conflict in East Borneo - Sharon Wilson,; Faridah Ibrahim, (Penerbit Universiti Kebangsaan Malaysia, 2018)
There is a continuous diplomatic cooperation between Malaysia and Philippines especially in relation to its involvement in a regional group called ASEAN. Nevertheless, there exist tensions and conflict with the emergence of a secessionist movement among the Philippines minority who insist on claiming territorial rights of Sabah. The February 2013 insurgency at Kampung Tanduo, Lahat Datu caused a conflict and triggered a bloody battle. Using in-depth interviews, document analysis and secondary data, this study explores the intensity in which journalists, Malaysian and Philippines were positioned in discovering the problems and challenged faced in gathering and reporting information as well as the decisions made during this time. It was found that the most critical aspect of decision making derives from professional ethics which govern the individuals. It is clear that the crime reporters’ loyalties lie not just to the profession but also to the people who employ them. The study has also successfully provided information which could be a source of reference for media practitioners and academicians and gives understanding not just the decision making of the reporter but the function and ethical aspects of reporting in a sensational field like conflict and war zones. This study can serve as a model for evaluation when implementing policies and training and the findings can be used by advisory committees especially in addressing issues of journalists reporting on national security.